The Effect of Interval Training Based on Heart Rate Variability (HRV) on Sleep Quality After Aerobic Exercise - Muh. Nur Fajar Arsyad; Syamsiah Syamsiah (International Journal of Experimental Sports Science Research, 2025)
Background: Sleep quality is an essential component of post-exercise recovery, particularly following high-intensity physical activities such as aerobic exercise. Autonomic nervous system regulation, commonly assessed through Heart Rate Variability (HRV), has been associated with recovery efficiency and sleep regulation. However, empirical evidence on the application of HRV-based interval training as a recovery strategy to improve sleep quality after aerobic exercise remains limited, particularly among adult women participating in community-based exercise programs. Objectives: This study aimed to analyze the effect of HRV-based interval training on sleep quality following aerobic exercise among members of the Bunda Antang aerobic exercise group. Methods: This study employed a quantitative approach using a Pre-Experimental One Group Pretest-Posttest Design. The participants consisted of 25 women aged 35–45 years selected through purposive sampling from the Bunda Antang aerobic exercise community. The intervention was conducted over six weeks using HRV-based interval training, in which exercise intensity and recovery intervals were individually adjusted according to real-time HRV monitoring. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), while HRV parameters were measured using a chest-strap heart rate sensor connected to HRV analysis software. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and Paired Sample t-Test at a significance level of α = 0.05. Results: The findings revealed significant improvements in sleep quality and HRV parameters following the intervention. PSQI global scores decreased from 11.84 ± 2.31 to 7.12 ± 2.04, representing a 39.86% improvement (p = 0.000). RMSSD values increased from 28.46 ± 6.72 ms to 41.93 ± 7.85 ms, representing a 47.33% improvement (p = 0.000). The largest improvement in PSQI components was observed in sleep latency, while RMSSD showed the most substantial increase among HRV parameters. Conclusions: HRV-based interval training significantly improves sleep quality and autonomic recovery following aerobic exercise. These findings indicate that HRV-based interval training is an effective recovery strategy for enhancing sleep quality among adult women engaged in community-based aerobic exercise programs.